Mid-infrared imaging in breast cancer tissue: an objective measure of grading breast cancer biopsies - Amrania,H; Woodley-Barker,L; Goddard,K; Rosales,B; Shousha,S; Thomas,G; McFarlane,T; Sroya,M; Wilhelm-Benartzi,C; Phillips,CC (Convergent Science Physicsl Oncology, 2018)
Introduction: -The majority of cancers are diagnosedusingexcised biopsy specimens. These are graded, using a gold-standard histopathology protocol based onhaemotoxylin and eosin (“H+E”)chemical staining. Howeverthe grading is done by eye and if the same biopsy is graded by differentpractitioners, they typically only agree ~70% of the time. The resultingovertreatment problem constitutes a massive unmet need worldwide.Objective:-Ournew ‘Digistain’technology, uses mid-infrared imaging to mapthe fractional concentration of nucleic acids, i.e. the nuclear-to-cytoplasmic chemical ratio (NCR) across an unstained biopsy section. It allows a quantitative “Digistain index” (DI) score, corresponding to the NCR, to be reproducibly extracted from an objective physical measurement of a cancer. Our objective here is to evaluate itspotential for aiding cancer diagnosis for the first time. We correlate the DI scores with H+E grades in a double-blind clinical pilot trial.Methods:-Two adjacent slices were taken from 75 breast cancer FFPE blocks; one was graded with the standard H+E protocol, and also used to define a “Region of Interest” (RoI). Digistain was then used to acquire a DI value averaged over the corresponding RoI on the other (unstained) sliceand theresults werestatistically analysed.Results:-We find the DI score correlates significantly (p=0.0007) with tumorgradein a way that promises to significantly reduce the inherent subjectivity and variability in biopsy grading.Discussion: The NCR is elevated by increased mitotic activity because cells divide when they are youngerand, on average, becomesmaller asthe disease progresses. Also, extra DNA and RNA is generated as thenuclear transcription machinery goes awry and nuclear pleomorphism occurs. Both effects make the NCR a recognized biomarker for a wide range of tumors